122 Relationship Between Coronary Microvascular Dysfunction, Myocardial Oxygenation and Abnormal Myocardial Energetics at Rest and Stress in Patients with Type 2 Diabetes Mellitus. (6th June 2015) - Levelt, Eylem; Holloway, Cameron; Rodgers, Christopher; Clarke, William; Mahmod, Masliza; Ariga, Rina; Francis, Jane; Liu, Alexander; Robson, Matthew; Clarke, Kieran; Karamitsos, Theodoros; Neubauer, Stefan
Abstract : Background: We and others have previously shown impaired myocardial energetics (decreased PCr/ATP using cardiac 31P Magnetic Resonance Spectroscopy [MRS]) in patients with type 2 diabetes mellitus (T2DM) at rest. Diabetic patients are known to have impaired myocardial perfusion reserve due to microvascular dysfunction even in the absence of epicardial coronary artery disease (CAD). There is yet no evidence whether this hypoperfusion is translated to myocardial deoxygenation and further energetic derangement at stress, i.e. true tissue ischaemia. We aimed to assess if the pre-existing energetic deficit in patients with uncomplicated T2DM is further exacerbated during exercise and to establish its relationship to myocardial perfusion and oxygenation during adenosine stress. Methods: 31 patients (mean age 55 ± 2 years; BMI 29 ± 1.0 kg/m 2 ) with T2DM and 24 matching controls (mean age 50 ± 3 years; BMI 27 ± 3 kg/m 2 ) were studied. Patients were on oral antidiabetic therapies only, with mean HBA1c 7.7 ± 0.3%. Obstructive CAD (>50% lumen diameter obstruction) was excluded in all patients by CT coronary angiography. Cardiac 31P-MRS (3T) was performed at rest and during 8 min of leg exercise lying prone, with 2.5 kg weights attached to both legs. Oxygenation-sensitive CMR (using a T2-prepared sequence) and first-pass perfusion images (using a saturation recovery fast-gradient echo sequence and 0.03 mmol/kg bolus of Gadoterate meglumine were also acquired at stress (3–6 min i.v. adenosine, 140 μg/kg/min) and rest. Signal intensity change (SIΔ) and myocardial perfusion reserve index (MPRI) were measured from oxygenation and perfusion images, respectively. Results: Left ventricular ejection fraction (LVEF) and mass index (LVMI) were similar in patients and controls (LVEF 69 ± 2 vs 70 ± 1%, P = ns; LVMI 60 ± 2 vs 52 ± 4 g/m 2, P = ns). Increases in rate pressure product with exercise (T2DM 46 ± 36%, controls 42 ± 26%, P = 0.825) and adenosine stress (T2DM 40 ± 3%, controls 39 ± 3%, P = 0.89) were similar. There was no change in PCr/ATP during exercise in controls (rest: 2.07 ± 0.1, exercise: 2.25 ± 0.1, P = 0.098). Resting PCr/ATP was reduced in patients (1.74 ± 0.1, P = 0.001) compared to controls, and during exercise, there was a further reduction in PCr/ATP (1.54 ± 0.1, P = 0.005) vs rest. As expected, myocardial perfusion reserve was significantly reduced in diabetic patients (1.61 ± 0.1 vs 2.19 ± 0.2 in controls, P = 0.002). Myocardial oxygenation was also impaired (SIΔ: T2DM 7.3 ± 1.4%; normal 17.1 ± 1.8%, P < 0.001). BOLD SIΔ and MPRI assessments correlated with exercise energetics (r = 0.312, P < 0.05; r = 0.481, P < 0.005 respectively), but not with rest energetics. Conclusions: During exercise, the pre-existing energetic deficit in patients with T2DM is further exacerbated. While myocardial energetics at rest is not related to coronary microvascular dysfunction and is primarily a result of metabolic dysfunction, during exercise, microvascular dysfunction exacerbates the energetic deficit.